The standardized extract of Centella asiatica L. Urb attenuates the convulsant effect induced by lithium/pilocarpine without affecting biochemical and haematological parameters in rats - Eduardo Rivadeneyra-Domínguez; Isaac Zamora-Bello; Juan Manuel Castañeda-Morales; Joel Jahaziel Díaz-Vallejo; Óscar Rosales-Sánchez; Juan Francisco Rodríguez-Landa (BMC, 2023)
Abstract Background Status epilepticus (SE) is a type of epileptic activity characterized by a failure of the inhibitory mechanisms that limit seizures, which are mainly regulated by the GABAergic system. This imbalance increases glutamatergic neurotransmission and consequently produces epileptic activity. It is also associated with oxidative stress due to an imbalance between reactive oxygen species (ROS) and antioxidant defences. Unfortunately, long-term treatment with anti-epileptic drugs (AEDs) may produce hepatotoxicity, nephrotoxicity, and haematological alterations. In this way, some secondary metabolites of plants have been used to ameliorate the deterioration of nervous system disorders through their antioxidant properties, in addition to their anticonvulsant effects. An example is Centella asiatica, a plant noted to have a reputed neuroprotective effect related to its antioxidant activity. However, similar to conventional drugs, natural molecules may produce side effects when consumed in high doses, which could occur with Centella asiatica. Therefore, we aimed to evaluate the effect of a standardized extract of Centella asiatica L. Urb with tested anticonvulsant activity on biochemical and haematological parameters in rats subjected to lithium/pilocarpine-induced seizures. Methods Twenty-eight adult male Wistar rats were randomly divided into four groups (n = 7 each): vehicle (purified water), Centella asiatica (200 and 400 mg/kg), and carbamazepine (CBZ) (300 mg/kg) as a pharmacological control of anticonvulsant activity. Treatments were administered orally every 24 h for 35 consecutive days. On Day 36, SE was induced using the lithium/pilocarpine model (3 mEq/kg, i.p. and 30 mg/kg s.c., respectively), and the behavioural and biochemical effects were evaluated. Results Centella asiatica 400 mg/kg increased the latency to the first generalized seizure and SE onset and significantly reduced the time to the first generalized seizure compared to values in the vehicle group. Biochemical parameters, i.e., haematic cytometry, blood chemistry, and liver function tests, showed no significant differences among the different treatments. Conclusion The dose of Centella asiatica that produces anticonvulsant activity in the lithium/pilocarpine model devoid of hepatotoxicity, nephrotoxicity, and alterations in haematological parameters suggests that the standardized extract of this plant could be of utility in the development of new safe therapies for the treatment of convulsions associated with epilepsy.